Coccinellids (Coleoptera: Coccinellidae) in citrus groves in Portugal: listing and analysis of geographical distribution - Magro, A.=700 1 Araéjo, J.; Hemptinne, J. L.
Resumenes (Es, En)
3 cuadros; 37 ref.
Keywords: COCCINELLIDAE; CONTROL DE PLAGAS; CONTROL BIOLOGICO; SCYMNUS; COCCIDOS